Transcriptomic analysis using RNA sequencing and phenotypic analysis of Salmonella enterica after acid exposure for different time durations using adaptive laboratory evolution - Ghoshal, Mrinalini; Bechtel, Tyler D.; Gibbons, John G.; McLandsborough, Lynne (Frontiers in Microbiology, 2024)
Introduction This study is the final part of a two-part series that delves into the molecular mechanisms driving adaptive laboratory evolution (ALE) of Salmonella enterica in acid stress. The phenotypic and transcriptomic alterations in the acid-evolved lineages (EL) of Salmonella enterica serovar Enteritidis after 70 days of acid stress exposure were analyzed. Materials and methods The stability of phenotypic changes observed after 70 days in acetic acid was explored after stress removal using a newly developed evolutionary lineage EL5. Additionally, the impact of short-term acid stress on the previously adapted lineage EL4 was also examined. Results The results indicate that the elevated antibiotic minimum inhibitory concentration (MIC) observed after exposure to acetic acid for 70 days was lost when acid stress was removed. This phenomenon was observed against human antibiotics such as meropenem, ciprofloxacin, gentamicin, and streptomycin. The MIC of meropenem in EL4 on day 70 was 0.094 mM, which dropped to 0.032 mM when removed from acetic acid stress after day 70. However, after stress reintroduction, the MIC swiftly elevated, and within 4 days, it returned to 0.094 mM. After 20 more days of adaptation in acetic acid, the meropenem MIC increased to 0.125 mM. The other human antibiotics that were tested exhibited a similar trend. The MIC of acetic acid in EL4 on day 70 was observed to be 35 mM, which remained constant even after the removal of acetic acid stress. Readaptation of EL4 in acetic acid for 20 more days caused the acetic acid MIC to increase to 37 mM. Bacterial whole genome sequencing of EL5 revealed base substitutions in several genes involved in pathogenesis, such as the phoQ and wzc genes. Transcriptomic analysis of EL5 revealed upregulation of virulence, drug resistance, toxin-antitoxin, and iron metabolism genes. Unstable Salmonella small colony variants (SSCV) of S. Enteritidis were also observed in EL5 as compared to the wild-type unevolved S. Enteritidis. Discussion This study presents a comprehensive understanding of the evolution of the phenotypic, genomic, and transcriptomic changes in S. Enteritidis due to prolonged acid exposure through ALE.